Implementation of diversion in case resolution children to realize protection law against children - LUBIS, MUHAMMAD RIDWAN; SIREGAR, GOMGOM T.P (The journal of contemporary issues in business and government, 2021)
The substance of the law of Law No. 11 of 2012 on the Juvenile Criminal Justice System determines that in the settlement of child criminal cases must be carried out diversion by law enforcement officials. The implementation of diversion is carried out at every level of the child criminal justice process. However, in the SPSA Act, not all cases done by children can be implemented diversion. In this case the law determines the limits of the qualifications of crimes that can be carried out diversionary in the settlement of child cases. The problems in this study, concerning the factors that influence the implementation of diversion and how the qualifications of criminal acts committed by children, as well as efforts to protect children in the settlement of child cases through the implementation of diversion. This type of research is empirical normative juridical research, by conducting research at the Medan Resort Police. This research is descriptive analysis, using primary and secondary sources. Data analysis used in this research is qualitative data analysis. The implementation of diversion is influenced by law enforcement factors and the legal culture of the community. From the aspect of law enforcement, human resources law enforcement apparatus still does not support the implementation of diversion through restorative justice approach. In addition, the implementation of diversion is also influenced by the difficulty of reaching a peace agreement between the victim and the perpetrator, due to the attitude of the perpetrator who is less cooperative and the victim or family who demands compensation outside the limits of the perpetrator's ability. The limitation of the qualification of crimes that can be implemented diversion in the child criminal justice system is, the crime is threatened with imprisonment of under 7 (seven) years and is not a repeat of the crime. The implementation of diversion in the resolution of ABH cases through restorative justice approach will provide protection to children. The implementation of diversion in the settlement of ABH cases will prevent children from formal criminal justice proceedings and also prevent children from the bad stigma that arises in the community towards children, as a result of the punishment by the court against the child.